KELAYAKAN HANDOUT STRUKTUR DAN FUNGSI JARINGAN TUMBUHAN DENGAN TAMBAHAN DISTRIBUSI STOMATA DAN LAJU TRANSPIRASI - Novi Salina; Entin Daningsih; Reni Marlina (EduNaturalia: Jurnal Biologi dan Kependidikan Biologi, 2022)
This study aimed to determine the feasibility of handout of submaterial structure and function of plant tissue with additional information about the stomatal distribution and transpiration rate used as teaching material. The research method used a descriptive. The validation was conductive by 5 validators and the validator was divided into two, namely the instrument validator and the handout teaching material validator. The instrument validator consisted of 2 Biology Education lecturers at FKIP UNTAN and 1 high school biology teacher in senior high school grade XI pontianak. The handout teaching material validator consisted of 2 Biology Education lecturers at FKIP UNTAN and 3 biology teachers senior high school grade XI pontianak using the 2013 curriculum and school accreditation A. The assessment used 5 aspects and 10 criteria. The results of handout validation of structure and function of plant tissue submaterial in senior high school grade XI of teaching materials with additional information based on the stomatal distribution and the transpiration rate in six monocot plants obtained an average CVR and CVI results 0.99 categorized valid and feasible to be used in the learning process. However, further research was needed on the effectiveness of learning outcomes used handout teaching materials in the learning process.